Un nuevo paradigma de justicia - Llerena, V. Herly (2019)
We are all aware of how the majority of Peruvians rejects corruption, entrenched in the national System of Justice. We are also aware of the fact that its institutions, in spite of increasing criticism and a clamor for change, have done practically nothing, logically, in the name of institutional reform. This essay proposes to combat corruption institutionally by analyzing comprehensively the current System of Justice, based on .the “levels of conscience” of organizations, in terms of which, upon revision of their characteristics and features, for example, it would be possible to  determine the causes or the vulnerabilities of the institutions directly involved, such as the Judiciary, the Office of the Attorney General, and the National Council of the Magistrate. This proposal includes introducing into the System of Justice technological innovations that have been successfully used in other justice systems, such as a software that helps to resolve conflicts quickly, economically, transparently, and safely.